2014
DOI: 10.1038/nsmb.2906
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for U2AF to define 3′ splice sites and regulate alternative splicing in the human genome

Abstract: The U2AF heterodimer has been well studied for its role in defining functional 3′ splice sites in pre-mRNA splicing, but many fundamental questions still remain unaddressed regarding the function of U2AF in mammalian genomes. Through genome-wide analysis of U2AF-RNA interactions, we report that U2AF has the capacity to directly define ~88% of functional 3′ splice sites in the human genome, but numerous U2AF binding events also occur in intronic locations. Mechanistic dissection reveals that upstream intronic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
185
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(222 citation statements)
references
References 46 publications
35
185
2
Order By: Relevance
“…A recent report has demonstrated that upstream intronic binding of U2AF 65 interferes with the immediate downstream 3′ splice-site of alternative exon or constitutive exon, causing exon skipping or inclusion (32). We found that intron 6 of SMN1/2 that includes uucuuuuuuuuuuuuuuuuuuuuuugag sequence contains pseudoexon with a potential U2AF 65 binding sequence; thus, according to the report, this sequence interferes with the 3′ splice-site of exon 7, thereby promoting an exon 7 skipping event (Fig.…”
Section: U2af 65 Promotes Its Own Binding Only On the Weaker Py Tractmentioning
confidence: 81%
See 1 more Smart Citation
“…A recent report has demonstrated that upstream intronic binding of U2AF 65 interferes with the immediate downstream 3′ splice-site of alternative exon or constitutive exon, causing exon skipping or inclusion (32). We found that intron 6 of SMN1/2 that includes uucuuuuuuuuuuuuuuuuuuuuuugag sequence contains pseudoexon with a potential U2AF 65 binding sequence; thus, according to the report, this sequence interferes with the 3′ splice-site of exon 7, thereby promoting an exon 7 skipping event (Fig.…”
Section: U2af 65 Promotes Its Own Binding Only On the Weaker Py Tractmentioning
confidence: 81%
“…We deduce that the stimulatory effects of U2AF 65 on alternative exon exclusion are induced by the splicing inhibitory effects of U2AF 65 . of alternative or constitutive exons to cause exon skipping or inclusion (32). In the SMN pre-mRNA, it was demonstrated that U2AF 65 interacts more strongly with the SMN1 Py tract than the SMN2 Py tract (33).…”
Section: Significancementioning
confidence: 99%
“…4). Considering that U2AF1 mutations are reported in B10% of patients with MDS and associated with partial functional impairment in regulated splicing 2,19 , we tested two MDS samples each harbouring one of the two U2AF1 hotspot mutations, S34F and Q157P. Neither of these MDS samples presented any increase of the AG 0 /AG index of DPH5, demonstrating that U2AF1 and SF3B1 hotspot mutations do not lead to the same aberrant splicing phenotype (Fig.…”
Section: Sf3b1 Mutations Promote Upstream Alternative Acceptorsmentioning
confidence: 99%
“…The insertion was identical to the U2snRNP binding region (20), and this finding may provide insight into why the ratio of FLIP isoforms is skewed toward cFLIP R in MSM mice. Indeed, genomewide RNA sequencing revealed a relative abundance of the long FLIP transcript in MSM mice and significantly more FLIP R mRNA in B6 mice, thus suggesting that splicing of FLIP in MSM/Ms is preferentially skewed toward spliced FLIP L mRNA.…”
Section: Significancementioning
confidence: 92%
“…In MSM/Ms mice, there is also the presence of a U2AF putative binding site in close proximity to the introduced U2 binding site (Fig. S2)-suggesting that, compared with B6, MSM/Ms may recruit the spliceosome complex more efficiently in this region, either leading to more efficient splicing of the intronic region between exons 5 and 6-producing more cFLIP L transcript-or creating an exon-skipping event of Exon 6 (20) leading to an ineffective transcript, or possibly making it physically difficult for the transcription of cFLIP R , either way decreasing the total amount of cFLIP R transcript that is produced. Although the 21-bp insertion is not conserved in humans, human data from the 1000 Genomes Project showed that there are SNPs within the 3′ UTR of the terminal exon for cFLIR R that may alter the binding sequence for U2 as well as for U2AF (Fig.…”
Section: Msm Micementioning
confidence: 99%